Signalling hypoxia by HIF hydroxylases. - Schofield, C; Ratcliffe, P (2005)
Analysis of oxygen sensitive pathways that regulate the hypoxia inducible factor (HIF) transcriptional system has revealed a novel role for oxygenases in signalling hypoxia. The enzymes, which catalyse hydroxylation of specific prolyl and asparaginyl residues in the regulatory HIF-alpha subunits, belong to the superfamily of non-haem Fe(II)-dependent oxygenases that use the citric acid cycle intermediate 2-oxoglutarate (2OG) as a co-substrate. We review biochemical and physiological data that demonstrate a central role for these oxygenases in integrating multiple signals that coordinate cellular responses to hypoxia.